Pemberdayaan Komunitas UMKM ‘Usaha Mandiri Sakinah’ Nogotirto, Gamping, Sleman DIY Menuju UMKM Yang Berdaya Saing: Pemberdayaan Komunitas UMKM ‘Usaha Mandiri Sakinah’ Nogotirto, Gamping, Sleman DIY Menuju UMKM Yang Berdaya Saing - Nur Faidati; Muhammad Khozin (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2020)
The fourth industrial revolution has taken a big leap for the industrial sector, where information and communication technology is fully utilized. MSME as an affected part of the industrial revolution needs to be prepared properly so that the products it produces can compete. MSME Community Independent Business Sakinah ’Nogotirto, Gamping, Sleman DIY is a MSME community that is fostered by oleh Aisyiyah University, Yogyakarta. This community still has obstacles in utilizing technology in developing its business in the industrial revolution era 4.0. Community service activities for the Community Empowerment of MSMEs 'Sakinah Independent Business' Nogotirto, Gamping, Sleman DIY Towards Competitive MSMEs are carried out with the aim of introducing a digital platform to members of the MSME community to market their products. The method used in this community empowerment activity is a workshop. The workshop was held 3 times. The first workshop was related to the common vision of business development of women entrepreneurs. The second workshop was related to the industrial revolution 4.0 and the use of online media for marketing (marketplace and social media). The third workshop, sharpening material on the use of technology as a marketing medium and making sales accounts in the Tokopedia marketplace. A number of advanced programs are still needed to equip members of the MSME community to produce quality products that are able to compete in the online market.